A paradigmatic model for shared value innovation management in the supply chain: A grounded theory research. Issue 1 (24th February 2020) - Rasti Borazjani Faghat, Ebrahim; Khani, Naser; Alemtabriz, Akbar
Abstract : Purpose: The purpose of this paper is to propose a paradigmatic model for shared value innovation management in the supply chain. This research seeks to identify the causal conditions, strategies, contextual factors, intervening factors and the consequences of shared value innovation in the supply chain. Design/methodology/approach: The approach of this research is qualitative and has been carried out in the framework of the grounded theory. Required data for the research was collected through semi-structured interviews. Coding was done in two steps and the reliability of the results of the research was confirmed by calculating the similarity index of codes by two methods. Findings: The proposed framework is presented in the form of a paradigmatic model and demonstrates how to achieve shared value innovation through increasing adoption with customer considerations, improving communication between supply chain members, improving collaboration among supply chain members, enhancing trust among supply chain members, enhancing the commitment of the supply chain members, enhancing supply chain members' interdependence while maintaining their independence and simultaneously reducing costs. The results of the analysis showed that the shared value innovation leads to positive consequences such as increasing competitive abilities, human development, synergy, inclusive growth and development and also the sustainability of the business situation. Originality/value: Although some studies have shown the importance of value innovation in different parts of the organization and to some extent the introduction of shared value innovation, no research has been done to provide a framework or model for managing shared value innovation.